Increasing access to mental health supports for healthcare workers during the COVID-19 pandemic and beyond through a novel coaching program - Arnold, Kimberly T.; Becker-Haimes, Emily M.; Wislocki, Katherine; Bellini, Lisa; Livesey, Cecilia; Kugler, Kelley; Weiss, Michal; Wolk, Courtney Benjamin (Frontiers in Psychiatry, 2022)
The COVID-19 pandemic led to heightened anxiety, distress, and burnout among healthcare workers and faculty in academic medicine. Penn Medicine launched Coping First Aid (CFA) in March 2020 in response to the pandemic. Informed by Psychological First Aid principles and therapeutic micro skills, CFA was designed as a tele-mental healthcare service for health system employees and their families delivered by trained lay volunteer coaches under the supervision of licensed mental health clinicians. We present an overview of the model, feasibility and utilization data, and preliminary implementation and effectiveness outcomes based on cross sectional coach (n = 22) and client (n = 57) self-report surveys with a subset of program users in the first year. A total of 44 individuals completed training and were certified to coach. Over the first 24 months of the program, 513 sessions occurred with 273 clients (119 sessions were no-shows or cancelled). Follow-up appointments were recommended in 52.6% (n = 270) of sessions and 21.2% (n = 109) of clients were referred for professional mental health care. Client survey respondents reported CFA was helpful; 60% were very or extremely satisfied, and 74% indicated they would recommend the program. Our preliminary findings suggest that CFA was feasible to implement and most clients found the service beneficial. CFA provides a model for rapidly developing and scaling mental health supports during and beyond the pandemic.